Institutional Satisfaction and Anxiety Mediate the Relationship Between Social Support and Depression in Hypertension Patients in Elderly Caring Social Organizations: A Cross-Sectional Study - Ji, Kai; Bai, Zhongliang; Tang, Ling; Yan, Huosheng; Zhu, Ying; Chen, Guimei; Chen, Ren (Frontiers in Psychology, 2021)
Background: Depression is a prevalent health condition among hypertension patients in elderly caring social organizations (SOs). Patients with hypertension and depression symptoms have worse health outcomes than those without depression. As the population ages, chronic and mental health issues such as depression of hypertension patients in elderly caring SOs have become prominent. However, the combined effects of social support, institutional satisfaction, and anxiety on depression among hypertension individuals in elderly caring SOs remain unclear. This study aimed to explore the mediating effects of institutional satisfaction and anxiety on the relationship between social support and depression among hypertension patients in elderly caring SOs in Anhui Province, China. Methods: A cross-sectional study was conducted using a multi-stage stratified random sampling method. A questionnaire was used to collect data on demographic characteristics, the satisfaction of elderly caring SOs, social support, anxiety, and depression. A multiple linear regression model was utilized to investigate depression-related factors, and structural equation modeling (SEM) was employed to examine the relationships between social support, institutional satisfaction, anxiety, and depression among patients with hypertension in elderly caring SOs. Results: Our results indicated that the mean scores of social support were 20.19 ± 6.98 and 1.92 ± 3.18 for anxiety, and 6.24 ± 5.03 for depression; besides, 33.3% of participants were very satisfied with elderly caring SOs, 48.5% were satisfied, and only 6.0% were dissatisfied or very dissatisfied. Comorbid chronic diseases were significantly associated with depression. Institutional satisfaction was directly negatively related to depression, whereas anxiety was directly positively correlated with depression. Social support had an indirect negative association with depression by the mediating effects of institutional satisfaction and anxiety. Conclusions: The study highlights the importance of social support in maintaining mental health among hypertension patients residing in elderly caring SOs. To alleviate depression among hypertension patients in elderly caring SOs, strategies that target enhancing social support, institutional satisfaction, and anxiety reduction should be prioritized. More importantly, more attention should be paid to patients with comorbid chronic diseases.